P76 Management of Giant Coronary Artery Aneurysms as a Coronary Sequelae of Kawasaki Disease – Surgical or Conservative Management?. (8th April 2021) - Quek, Fang Fang; Tulloh, Robert; Quek, Fang Fang
Abstract: Introduction: Kawasaki Disease (KD) is the commonest childhood acquired heart disease in developed countries, predominantly affecting children younger than 5 years' of age. These patients are at high risks of developing coronary arterial aneurysms (CAA) and CAA with absolute internal luminal diameters measuring ≥8mm or Z-score ≥10 are classified as giant coronary aneurysms (GCA). Case Report: A 19-year-old girl with previous history of Kawasaki disease was diagnosed with giant coronary aneurysms on echocardiograms. Her subsequent CT coronary angiography showed large aneurysms in the right coronary artery (29mm x 25mm) and left anterior descending artery (10mm x 10mm) with signs of calcification. However, surprisingly, despite the evidence of large coronary aneurysms, she was completely asymptomatic and was physically active, participating in competitive sports. Her cardiac MRI scan 17 years after KD onset showed right coronary perfusion deficit in the distal right coronary territory but with no evidence of myocardial infarction. A repeated cardiac CT was performed and showed delayed filling of the distal right coronary artery. However, it was uncertain at this point if the aneurysm was causing true ischaemia or simply delayed perfusion. An ECG stress test was subsequently performed for further investigation which showed no significant abnormality. After having a detailed discussion in the MDT and with colleagues from San Diego, USA, a conservative approach was decided to be in the patient's best interest. She has been advised to avoid competitive or strenuous exercise due to the associated risks. She is fit-and-well, and is currently on Warfarin variable dose and Aspirin 75mg OD, with annual cardiac MRI surveillance. Discussion: 20% of KD patients develop CAA and approximately 5% of KD patients have evidence of GCA. Unlike small and medium CAA, GCA regress in a much slower and more constant rate, and they never achieve complete resolution. A Japanese retrospective study showed the 10-year coronary event-free survival rates in small, medium and giant CAA as 100%, 96% and 61% respectively (p<.001). Patients with GCA are at significantly increased risks of coronary complications and major cardiac events (48%). Despite maximal medical treatment, patients with GCA have high risks of aneurysm rupture which is associated with high mortality rates. These patients are also at lifelong risks of atherosclerosis and stenosis which may lead to myocardial ischaemia and even death. Therefore, it is absolutely essential to control for cardiovascular risk factors and adhere to strict treatment regime. These patients also require lifelong, uninterrupted cardiology follow-up in a specialist KD clinic. Catheter and surgical interventions may be indicated in some patients. There have been recent attempts in combining CABG with downsizing reconstruction for GCA in an attempt to decrease GCA diameter and improve the coronary flow rate to prevent thrombosis which has shown quite promising results. However, the decisions whether to undergo a surgical intervention should be tailored to each individual, taking into consideration all aspects of a patient, including their disease status and social life. Conclusion: With an increasing prevalence of KD in UK, it is essential to always consider the diagnosis of KD in a febrile child with raised inflammatory markers, especially in patients presenting with prolonged fever (longer than 4-5 days) as a delay in commencing treatment poses a significantly increased risk of developing coronary complications which are associated with high morbidity and mortality rates.